NATION BRANDING “WONDERFUL INDONESIA” THROUGH COLLABORATION WITH TIKTOK TO PROMOTE INDONESIAN TOURISM - Wahyuni Maulida,; Resa Rasyidah, (International Journal of Social Science, 2024)
Nation branding is a country's effort to advance its identity so that other countries see it as having a positive image. Nation branding can help countries increase tourism, trade, investment, and tourism. Wonderful Indonesia is Indonesia's tourism promotion slogan, which was introduced in other countries as Indonesia's national brand. The Wonderful Indonesia program was created to increase tourism in 2014. From 2019 to 2021, foreign tourists experienced a drastic decline due to the COVID-19 pandemic. The government was trying to restore the Indonesian tourism sector by collaborating with TikTok. TikTok users continued to increase until 2019. TikTok has many fans around the world. This research used Anholt's Competitive Identity Nation Branding theory to analyze the Indonesian government's strategy in building Wonderful Indonesia nation branding through collaboration with TikTok to promote Indonesian tourism. The theory comprises six hexagonal elements: tourism, export brands, policy, investment, culture, and people. The goal was to promote Indonesian tourism nationally and internationally. This research used a qualitative research method of descriptive research type, using secondary data collection techniques